2006
DOI: 10.1557/proc-0933-g02-09
|View full text |Cite
|
Sign up to set email alerts
|

Charge Trapping Memory Cell of TANOS (Oxide-SiN-Al2O3-TaN) Structure Erased by Fowler-Nordheim Tunneling of Holes

Abstract: We present the TANOS (Si-Oxide-SiN-Al 2 O 3 -TaN) cell with 40 Å-thick tunnel oxide erased by Fowler-Nordheim (FN) tunneling of hole. Thanks to introducing high-k dielectrics, alumina (Al 2 O 3 ) as a blocking oxide, the erase threshold voltage can be maintained to less than -3.0 V, meaning hole-trapping in SiN. We extracted the nitride trap densities of electron and hole for the TANOS cell. It is demonstrated that the TANOS structure is very available to investigate the trap density with shallower energy. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
2
2
0
Order By: Relevance
“…The observation that μ CNTFET of transfer curves with applied pulse 1 is larger than that with applied pulse 2 may suggest that (1) pre-trapped holes have less effect on hole transport than pre-trapped electrons, or/and (2) the number of pre-trapped holes is much smaller than that of pre-trapped electrons. The latter suggestion is consistent with Lee et al's findings [25], where the number of trapped electrons is much larger than that of trapped holes in the Si 3 N 4 film. However, for the electronconduction branches, μ CNTFET under the influences of both pulse 1 and pulse 2 are comparable.…”
Section: Resultssupporting
confidence: 92%
“…The observation that μ CNTFET of transfer curves with applied pulse 1 is larger than that with applied pulse 2 may suggest that (1) pre-trapped holes have less effect on hole transport than pre-trapped electrons, or/and (2) the number of pre-trapped holes is much smaller than that of pre-trapped electrons. The latter suggestion is consistent with Lee et al's findings [25], where the number of trapped electrons is much larger than that of trapped holes in the Si 3 N 4 film. However, for the electronconduction branches, μ CNTFET under the influences of both pulse 1 and pulse 2 are comparable.…”
Section: Resultssupporting
confidence: 92%
“…After the surface passivation with the Si 3 N 4 layer, an ambipolar characteristic with a stable hysteresis loop in the transfer curve is observed for V gs in a range of −20 to +20 V, as shown in Figure a. The observed p-type to ambipolar conversion can be attributed to the removal of oxygen adsorbed on the DWNT channel by coating Si 3 N 4 . , This is consistent with the findings that desorption of oxygen by dielectric layer passivation or annealing CNTFETs in vacuum or inert gas promotes conversion from p- to ambipolar or even n-type. ,, In addition, it has been reported that the SiO 2 −Si 3 N 4 stacks play the role of trapping centers for both electrons and holes . The hysteresis loop is caused by the trapping/detrapping of electrons/holes in the trapping centers, and it is stable after passivation.…”
supporting
confidence: 86%
“…4,13,14 In addition, it has been reported that the SiO 2 -Si 3 N 4 stacks play the role of trapping centers for both electrons and holes. 15 The hysteresis loop is caused by the trapping/detrapping of electrons/holes in the trapping centers, and it is stable after passivation. Since our Raman spectra are collected from the center of the DWNT channel, the results of the Raman scattering should reflect the energy band shift (or, in an equivalent way, the Fermi level ε f shift) in the DWNT channel rather than any influences from the source and drain contacts.…”
mentioning
confidence: 99%
“…28 In addition, it has been reported that the SiO 2 -Si 3 N 4 stacks act as the trapping centers for both electrons and holes. 153 The hysteresis loop is caused by the trapping/detrapping of electrons/holes in the trapping centers and it is stable after passivation. Since our Raman spectra are collected from the center of the DWNT channel, the results of the Raman scattering should reflect the energy band shift (or, in an equivalent way, the Fermi level ε f shift) in the DWNT channel rather than any influences from the source and drain contacts.…”
Section: Methodsmentioning
confidence: 99%